EVOLUTIONAL-GENETIC APPROACH TO FORMATION OF SUSTAINABLE DEVELOPMENT INDICATORS OF THE AGRICULTURAL TERRITORIES - RASSADIN, Vladimir Vasilievich; PAVLOV, Aleksandr Jurievich; BATOVA, Vera Nikolaevna; KOLESNIKOV, Andrey Vladimirovich (Journal of Environmental Management and Tourism, 2016)
The system of sustainable development indicators of agricultural territories is substantiated in the article from the position of evolutionary-genetic approach. The sustainable development in many respects is determined by the stability of such constituents as labour resources, process of production, natural environment, legal, organizational-economic and information space. The sustainable development is represented by the function of economic potential and economic activity of population, residing in the agricultural territories. The factorial structure of source and relative indicators of economic potential and economic activity of population was considered. The development and realization of the programme of provision of the sustainable development in the region requires creation of the regional geoinformation systems and active usage of labour resources. It is necessary to name among priority tasks on creation of resources of space data in the form of bases of geodata as inventory and generalization of natural-resource, medico-biological and ecological information in the region, calculation and estimation of space sustainable development indicators of its agricultural territories.
Keywords: sustainable development; evolutional-genetic theory of production factors, economic potential; economic activity; agricultural territory